Identification of Drought Tolerance in Mutant Maize Genotypes to Ensure Raw Material Stability for the Food Industry - Andriyana Gustam; Suryansyah Surahman; Nur Hardina; Hamdani Muchtar (Universitas Islam Raden Rahmat, Malang, 2026)
Maize production stability in drought-prone environments is crucial to ensure continuous raw material supply for the food industry. This study aimed to evaluate the interaction between mutant maize genotypes and different water availability levels to identify drought-tolerant genotypes during the vegetative growth stage. The experiment was conducted in a screen house at the Faculty of Agriculture, Hasanuddin University, using a factorial split-plot design with three replications. Water availability levels (60%, 80%, and 100% of field capacity) were assigned as main plots, while six maize genotypes were arranged as subplots. Analysis of variance (ANOVA) revealed a highly significant interaction (p ≤ 0.01) between genotype and water availability on root length, root volume, and flowering time. Under 60% field capacity, the Bisma 200 Gy genotype produced the longest root length (90.67 cm) and the highest root volume (116.67 mL), significantly exceeding the controls based on LSD at 1%. This genotype also showed lower leaf dryness and earlier male (51.94 days) and female (56.22 days) flowering. These findings demonstrate that Bisma 200 Gy exhibits enhanced drought tolerance through improved root development and accelerated flowering (drought escape), indicating strong potential as a stable maize raw material for water-limited environments.